2009
DOI: 10.1016/j.agrformet.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Airflow and microclimate patterns in a one-hectare Canary type greenhouse: An experimental and CFD assisted study

Abstract: This study presents an analysis of air circulation and microclimate distribution during daytime in a 1-hectare Canary type tomato greenhouse in the coastal area of southern Morocco. The investigation of the climate inside the greenhouse is based on a numerical simulation using a finite volumes method to solve the mass, momentum and energy conservation equations. The main novelty of this simulation lies in the realism of the 3D modelling of this very large agricultural structure with (i) a coupling of convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 28 publications
(18 reference statements)
10
54
0
4
Order By: Relevance
“…Rico-García et al (2008) showed that ventilation in greenhouses due to the temperature effect produces high air exchange rates; however, those air patterns occur near the openings, causing almost no air exchange in the central zone of the greenhouse due to a stagnant effect that reduces the wind effect throughout the greenhouse. In agreement with the results of Majdoubi et al (2009), convection and radiation are the dominant forms of heat transfer. The measurements show that the difference between the air temperature inside and outside the greenhouse is strongly linked to solar radiation and secondly to wind speed.…”
Section: Temperature and Air Exchangesupporting
confidence: 77%
See 3 more Smart Citations
“…Rico-García et al (2008) showed that ventilation in greenhouses due to the temperature effect produces high air exchange rates; however, those air patterns occur near the openings, causing almost no air exchange in the central zone of the greenhouse due to a stagnant effect that reduces the wind effect throughout the greenhouse. In agreement with the results of Majdoubi et al (2009), convection and radiation are the dominant forms of heat transfer. The measurements show that the difference between the air temperature inside and outside the greenhouse is strongly linked to solar radiation and secondly to wind speed.…”
Section: Temperature and Air Exchangesupporting
confidence: 77%
“…Wind speed had a linear influence on air exchange rates, while the wind direction did not affect them. Majdoubi et al (2009) observed a strong wind air current above a tomato canopy that was fed by a windward side vent and a slow air stream flowing within the tomato canopy space. The first third of the greenhouse, until the end of the leeward side, was characterized by a combination of wind and buoyancy forces, with warmer and more humid inside air that was removed through upper roof vents.…”
Section: Windward and Leeward Wind Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…CFDs can help designers in this task. A lot of papers have been recently published on this issue, many of them based on international research projects with collaboration of the countries with larger surfaces devoted to greenhouses such as Spain, Italy, Greece, the Netherlands, Israel or USA (Majdoubi et al, 2009;MolinaAiz et al, 2010).…”
Section: Computational Fluid Dynamics In Buildings and Infrastructurementioning
confidence: 99%